The state of the art of environmental economic water and forest accounts in Brazil: Overview and evolution - Geraldo Sandoval Góes; José Antônio Sena Nascimento; Vinicius Pacheco de Almeida; Mário Jorge Mendonça; Marco José Melo Neves (Institute for Applied Economic Research (ipea), 2021)
This paper aims to report the construction process of Environmental Economic Accounts for Water in Brazil and its institutional articulation between national and international public and private institutions, who participated in this construction effort. It also presents the current stage of construction of the Environmental Economic Accounts for Forest in Brazil.
Keywords: Q25; Q23; Q56; 330; SEEA; water; forest; Brazil